PENINGKATAN KETERAMPILAN MEMBACA MATA PELAJARAN PAI DENGAN METODE COOPERATIVE SCRIPT PADA SISWA SD - Roesmiatoen . (Universitas Islam Nahdlatul Ulama Jepara, 2022)
The validity of this research is that teachers have not been able to create a conducive and pleasant learning atmosphere during the learning process, the purpose of this study is (1) to describe the application of Cooperative Script learning methods in improving reading skills of Islamic Religious Education subjects of students of Grade IV Elementary School N 1 Panggang Jepara, (2) describing the improvement of reading skills of Islamic Religious Education subjects of students of Grade IV Elementary N 1 Panggang Jepara. This type of research is a Kemmis and Mc Taggart model class action research (PTK) consisting of two cycles (cycle 1 and cycle 2) that include planning, action, observation and reflection. Data collection techniques are carried out through interviews, observations, questionnaires (questionnaires) and tests. Data analysis techniques are carried out quantitatively and qualitatively, by reviewing all the data obtained through the results of tests and observations that have been done, Based on the results of research and discussion it can be concluded that there is an increase in students' reading skills and learning outcomes of students in grade IV elementary school N 1 Panggang Jepara. The average result of the analysis of student reading skills data is 72.25 can be categorized enough which then increases to 87.5 can be categorized well in cycle II. The average value of formative tests in cycle I is 65 with less categories increasing in cycle II to 90 with excellent categories.